2015
DOI: 10.1155/2015/750345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kamishoyosan, a Traditional Japanese Kampo Medicine, on Pain Conditions in Patients with Intractable Persistent Dentoalveolar Pain Disorder

Abstract: There are patients who suffer from persistent dentoalveolar pain disorder (PDAP) which is a pain of the teeth, either dentoalveolar pain or nonodontogenic toothache, and its cause has not yet been identified. An effective intervention for PDAP has not yet been established. Interventions for patients with PDAP are generally pharmacological treatments such as antidepressants, anticonvulsants, and pregabalin. However, these medicines are not always effective for patients. The pain disorder in the orofacial region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The 129 kinds of Kampo medicines can be divided into two groups: those with and without Bupleuri Radix (BR). KSS contains BR and is prescribed for climacteric disorder and orofacial pain [35,36]. In this study, we examined the effects of Hochuekkito (HET), Shoseiryuto (SST), and Goreisan (GRS), as the control of KSS.…”
Section: Kss Reduces Intracellular Lipid Accumulationmentioning
confidence: 99%
“…The 129 kinds of Kampo medicines can be divided into two groups: those with and without Bupleuri Radix (BR). KSS contains BR and is prescribed for climacteric disorder and orofacial pain [35,36]. In this study, we examined the effects of Hochuekkito (HET), Shoseiryuto (SST), and Goreisan (GRS), as the control of KSS.…”
Section: Kss Reduces Intracellular Lipid Accumulationmentioning
confidence: 99%
“…Kampo consists of a system of essentially three dichotomies and three substance concepts [3][4][5][6][7][8]. The three dichotomies are: Yin-You (yingyang), Kyo-Jitsu, and Netsu-Kan (translated into English as ''positive-negative'', ''hollow-full'', and ''hot-cold'', respectively).…”
Section: Kampo's Basic Conceptsmentioning
confidence: 99%
“…PDAP is effectively treated by using a unique exercise therapy for the improvement of jaw movement in combination with psychological intervention to reduce parafunctional activities. Kamishoyosan is a Kampo formula used to effectively treat psychological symptoms such as anxiety, irritability, and depression [5]. A prospective study showed that Kamishoyosan improved the pain intensity in 14 out of 15 PDAP patients refractory to the original exercise therapy.…”
Section: Kampo For Various Refractory Orofacial Painmentioning
confidence: 99%